MUC464 : Harmony II / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course is a continuation from Harmony I. Harmony II will give students more in-depth study on how to write and create music at an advance level. It exposes students to the various terms, principles and techniques of harmony. Students are also exposes to the various types of musical styles such as swing, blues, jazz, popular music, latin music, malay traditional/folk music and new age music.